Africa since decolonization : The history and politics of a diverse continent - Martin, Welz Dr (cambridge, 2021)
"The prologue highlights Africa's diversity, sets out the author's perspective on the subject, gives some reasons why it is worth studying African history and politics, and offers of short preview of the book"--